2005
DOI: 10.1002/jsfa.2189
|View full text |Cite
|
Sign up to set email alerts
|

Ensiling characteristics and aerobic stability of direct‐cut and wilted grass silages inoculated with Lactobacillus casei or Lactobacillus buchneri

Abstract: Two experiments were conducted to study the effects of wilting and inoculating Lactobacillus casei or Lactobacillus buchneri on the fermentation and aerobic stability of grass silages. Chopped Italian ryegrass (IR) and Festulolium (FE) were ensiled with or without wilting and added L casei (>10 6 cfu g −1 fresh matter (FM)) or L buchneri (>10 6 cfu g −1 FM). Silos were opened after 120 days and microbial counts, fermentation products and aerobic stability were determined. Addition of L casei increased lactic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
31
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 20 publications
5
31
1
1
Order By: Relevance
“…In fact, aerobic stability could be improved because acetic acid inhibits growth of specific species of yeast that are responsible for heating upon exposure to air. Similar results have also been reported by Taylor et al (2002) and with those obtained by Nishino and Touno (2005) with Italian ryegrass and Festilolium.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In fact, aerobic stability could be improved because acetic acid inhibits growth of specific species of yeast that are responsible for heating upon exposure to air. Similar results have also been reported by Taylor et al (2002) and with those obtained by Nishino and Touno (2005) with Italian ryegrass and Festilolium.…”
Section: Discussionsupporting
confidence: 91%
“…Similar effects were found by Nishino and Touno (2005) on wilted grass silages, and it was explained by gas losses during fermentation process. Interaction in DM content could be explained due to the fact that the proportional increase in DM in F was higher than in TF.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…We isolated Lactobacillus buchneri from stable TMR silage as a predominant lactic acid bacterium (LAB), and then found that the 1,2-propanediolproducing LAB can suppress aerobic deterioration of corn and grass silages (Nishino et al, 2003b(Nishino et al, , 2004Nishino and Touno, 2005). Although the reason why L. buchneri predominated during fermentation is unknown, our findings suggest that L. buchneri may account for the stability of BG-containing TMR silage.…”
Section: Introductionmentioning
confidence: 81%